THE EFFECT OF EMOTIONAL INTELLIGENCE ON THE ACADEMIC ACHIEVEMENT OF HIGH SCHOOL STUDENTS WITH LEARNING MOTIVATION AS A MEDIATING VARIABLE - Enggar Putri Kusuma; Santi Aji Astuti; Nur Ilmiyah Izzah; Rara Jufita Sari (P3I UMSurabaya, 2025)
This study examines the influence of emotional intelligence on academic achievement with learning motivation as a mediating variable among high school students. The research involved 320 students from three high schools in Surabaya, selected through stratified random sampling. Data were collected using the Emotional Intelligence Scale, Academic Motivation Scale, and academic achievement scores from school records. Path analysis using SPSS 26 and PROCESS Macro revealed that emotional intelligence significantly predicted academic achievement, and this relationship was partially mediated by learning motivation. The findings indicate that students with higher emotional intelligence tend to have better learning motivation, which subsequently contributes to improved academic performance. This study provides empirical evidence for the importance of integrating emotional intelligence development in educational curricula to enhance student academic outcomes.